The incidence of flipped learning in the development of the writing skill of senior english learning groups at johannes Lepler High School, 2014-2015 year - López López, Carla Monserrat (2015)
This study explores the incidence of Flipped Learning in the Writing Skill of ESL. It was designed to bring light to World Wide teachers upon the new opportunities of change we have with the unstoppable growth of ICT´s. This document aims to analyze what kind of influence, either positive or negative, the new model of Education, Flipped Learning, has upon the development of Writing Skill, designed for students belonging to a Private Institution and that may serve as a model to follow to other Private and Public Institutions as well. In addition, it provides a theoretical framework that analyzes some of the most important previous researches done on the matter. Further on, a proposal has been created based on a theoretical framework that includes a qualitative and quantitative analysis that aims to open workshops for teachers and students in order to increase the appliance of this method, by creating new didactical material to give support to this growth, also to help them use technologies in a more efficient way. Finally, it offers a program that recognizes teachers and students to be facilitators of further workshops for the new community members the school welcomes every year.